Treating alcohol-related violence: intermediate outcomes in a feasibility study for a randomized controlled trial in prisons - Bowes, Nicola (Criminal justice and behavior, 2012)
There is a lack of outcome evidence for alcohol interventions for offenders whose crime is alcohol related. In this study, the authors report the intermediate outcomes of a feasibility study for a randomized controlled trial of an alcohol-related violence intervention. Control of Violence for Angry Impulsive Drinkers (COVAID) was tested with sentenced prisoners in the United Kingdom. Participants were 115 adult men who were randomly allocated to COVAID or treatment as usual. Measures were the Alcohol-Related Aggression Questionnaire (ARAQ), the State-Trait Anger Expression Inventory (STAXI-2), the Eysenck Impulsivity, Venturesome, and Empathy Scale (IVE), and the Controlled Drinking Self-Efficacy Scale (CDSES). After the intervention, participants allocated to COVAID reported significantly greater improvement on the ARAQ Alcohol-Aggression subscale and all CDSES subscales. No significant differences were obtained for the STAXI-2 or the IVE. COVAID may have the potential to fill a gap in treatment provision for offenders whose crimes of violence are alcohol related.